2017
DOI: 10.1111/ijfs.13441
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of microemulsion nanofilms based on Tilapia fish skin gelatine and ZnO nanoparticles incorporated with ginger essential oil: meat packaging application

Abstract: Summary Microemulsion nanofilms based on fish skin gelatine (FSG) and 3% (w/w, gelatine) ZnO nanoparticles (ZnONP) incorporated with ginger essential oil (GEO) at different concentration (10%, 20%, 40%, 80%, w/w, gelatine) were developed and characterised. Film thickness and elongation increased, while film tensile strength and gel strength decreased as GEO level increased (P < 0.05). The water vapour permeability was reduced (P < 0.05) by GEO. Microstructural study revealed a dispersion system with GEO lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The impact of the combination treatments on these bacteria was both significant and strong. In consistence with our results, Zhang et al () proved the impact of edible coating containing GEO on LAB count decline, as well.…”
Section: Resultssupporting
confidence: 93%
“…The impact of the combination treatments on these bacteria was both significant and strong. In consistence with our results, Zhang et al () proved the impact of edible coating containing GEO on LAB count decline, as well.…”
Section: Resultssupporting
confidence: 93%
“…Essential oils and oleoresins extracted from the species Z. officinale are rich in diverse chemical compounds, such as zingiberene, α-curcumene, monoterpenes camphene, geranial, linalool, 1,8-cineole, which confer bioactivity as antioxidants and anti-inflammatory or antimicrobial extract [24]. Currently, ginger essential oil (GEO) is being used in studies aiming the development of novel active packaging materials to be used in the food industry: chitosan-carboxymethyl cellulose films incorporated with GEO and cinnamon EO [25]; nanofilms based on Tilapia fish skin gelatin and ZnO nanoparticles incorporated with GEO for meat packaging application [26]; nanoemulsion-based edible sodium caseinate coatings applied in fresh meat [27], edible coatings based on hydroxypropyl methylcellulose, beeswax, nanoclay and ginger oil applied in fresh mango cuts [28].…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al () also reported that corn zein/soya protein isolate bilayer film is effective to reduce the lipid oxidation of olive oil during storage at dry and intermediate RH. Zinc oxide nanoparticles with excellent dispersion in polymer matrix improved the resistance against the transfer of water and gases across the biodegradable film (Rouhi, Mahmud, Naderi, Ooi, & Mahmood, ; Zhang et al, ). Findings of Vejdan, Ojagh, and Abdallohi () also support the present investigation that the addition of TiO 2 nanoparticles in gelatin/agar bilayer films prevented the transmission of UV light through the film and so reduced the rate of photo oxidation of the fish oil during storage.…”
Section: Resultsmentioning
confidence: 99%